The New Normal in Pastoral Care: The Enduring Legacy of Media Appropriation in the Post-Pandemic Roman Catholic Church - Giulia Isetti; Michael de Rachewiltz; Harald Pechlaner (Religions)
By leveraging 20 semi-structured interviews conducted in 2020 and 2024 with parish priests and laypeople with an office in the Diocese of Bolzano-Bressanone (Italy), this paper explores the enduring legacy of the pandemic in terms of digital engagement in Roman Catholic pastoral activities. Additionally, it investigates the impact of ICT and AI on religious authority. A comparison of the two waves of interviews shows that in the new normal, there has been an acceleration of the adoption of ICT and AI, primarily for internal communication purposes. However, faithful engagement and interaction through new and old media have remained one-way, reinforcing current ecclesiastical power hierarchies. Despite some inherent theological limitations to a more participatory use of ICT, the presence of pockets of innovation in extra-sacramental activities points to future possibilities for empowering laypeople and engaging with the faithful without compromising Church doctrine.